THE POTENCY OF ANTITUBERCULOSIS ACTIVITY OF SECONDARY METABOLITES FROM GARUGA FLORIBUNDA AND ITS DERIVATIVES USING THE IN SILICO METHOD, ALONG WITH ITS ISOLATION AND TRANSFORMATION - Nurul Hidayah, Qolbu
Tuberculosis (TB) is a disease caused by the Mycobacterium tuberculosis (MTB) with high cases of drug resistance in patients (MDR/Multi Drug Resistant). TB treatment using isoniazid is considered less effective due to the presence of KatG mutation as an isoniazid activating catalyst on the InhA. Therefore, there is an urge to find alternative drugs, such as from plants, that directly inhibit InhA without the activation of KatG catalyst. One of the plant genus that has been widely used as a medicine for asthma and lung infections is Garuga. The main secondary metabolite from this genus, i.e. a cyclic diarylheptanoid, has been reported to have antibacterial activity. One species of Garuga growing in Indonesia is G. floribunda. A previous study on the heartwood of G. floribunda identified the presence of two cyclic diarylheptanoid compounds, namely alnusdiol and alnuson. Moreover, the prenylation of alnusdiol produced monoprenylated (AHS-1) has also been reported. In this research, the potency study of the inhibition ability of the cyclic diarylheptanoid and its transformation products towards InhA have been carried out using the in silico method. Those cyclic diarylheptanoids included alnusdiol, alnuson, AHS-1, and the product of transformation simulation of phenolic group on alnusdiol, i.e. allylation (AHS-2), benzylation (AHS-3), and the reaction with triethylene glycol monomethylether (ALN-1). In addition, the isolation of secondary metabolites of alnusdiol from Garuga floribunda was carried out in several steps, including maceration of heart wood powder with acetone solvent, fractionation of acetone extract and purification of the obtained fractions using various chromatographic techniques ((Vacuum Liquid Chromatography (VLC) and Gravity Column Chromatography (GCC)). Subsequently, the alnusdiol derivative with the best potential activity was also synthesized. The structure of the isolated compound and the alnusdiol derivative was characterized using NMR spectroscopy data. The results of the in silico study showed that the monobenzylation alnusdiol (AHS-3) product had the best inhibition potential with a docking score of ?9.9 kcal/mol. Hydrogen bonding and hydrophobic interactions that stabilize the complex between AHS-3 with InhA, in addition to the interaction of key residues on Tyr158. Moreover, the isolation of secondary metabolite from heart wood of Garuga floribunda yielded alnusdiol as the main product with mass of 104.1 mg (percent yield of 1.69 ×10-2%). The benzylation reaction of alnusdiol that was carried by reflux at 56 oC, produced alnusdiol monobenzylation (AHS-3) yield of 66,1%. The determination of the structure of the isolated compound and the transformed compound was carried out based on 1D-NMR spectroscopic data (1H-NMR and 13CNMR) showed that the isolated compound, i.e. alnusdiol, has been obtained and the benzylation reaction has occurred only in one phenolic group of alnusdiol.